54. ANALYSIS THE FACTORS RELATED TO SPECIMEN REJECTION AT THE LABORATORY DEPARTMENT (Vietnam Journal of Community Medicine, 2024)
Objective: The study focuses on identifying the proportion of rejected specimen and understanding the factors related to the rejection process.Subject and method: This is a retrospective descriptive study conducted at the Laboratory Department of HCMC Hospital For Rehabilitation – Professional Diseases. Data was collected from January 2023 to December 2023, encompassing 77,767 clinical specimens.Results: Out of 77,767 specimens, 289 (0.37%) were rejected. Among these, 83.39% of the rejected samples were due to quality issues, including coagulation and hemolysis, while 16.61% were rejected due to administrative errors, such as missing or incorrect information on the sample or test order form.Conclusion: The study found that most specimen rejections were due to quality issues, with fewer linked to administrative errors. Nurses, responsible for collecting, recording, preserving, and transporting specimens, play a critical role. Errors like incomplete documentation or improper collection techniques can increase rejection rates. Enhancing nurses' skills in specimen handling is vital to reducing rejections, improving lab quality, and ensuring accurate diagnostic results.
Keywords: Specimen rejection; Sample quality issues; Laboratory quality control